Think-Tank for Christians in Education: The Ministry of the Journal of Christian Education - Hill, Brian V. (Journal of Christian education, 2012)
In this article Brian Hill overviews the ministry of JCE in its contribution to the theory and practice of Christian thought on education. He does this by identifying the major themes which have been addressed by the journal over its history, highlighting those themes which have ‘recycled’ over the years as well as shorter-lived topics which were significant at the time. He helpfully sets the themes and associated articles in their historical educational and social context.